2019
DOI: 10.1029/2019jd030435
|View full text |Cite
|
Sign up to set email alerts
|

The ENSO and QBO Impact on Ozone Variability and Stratosphere‐Troposphere Exchange Relative to the Subtropical Jets

Abstract: The El Niño–Southern Oscillation (ENSO) and the Quasi‐Biennial Oscillation (QBO) are natural sources of ozone variability in the tropical and midlatitude upper troposphere and lower stratosphere. Regional tropospheric ozone variations have previously been attributed to ENSO‐ and QBO‐induced changes in stratosphere‐troposphere exchange around the subtropical jets (STJs). We use Goddard Earth Observing System Data Assimilation System analyses of Ozone Monitoring Instrument and Microwave Limb Sounder ozone data m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
(98 reference statements)
0
18
0
Order By: Relevance
“…No major volcanic eruption occurred during the analysed period, so we disregard this source of variability. The influence of the QBO and ENSO on the hemispheric mean mid-latitude ozone is of the same magnitude, and thus they can both impact LS ozone trends, as shown by the study of Olsen et al (2019). We know from earlier studies that the QBO has a strong dynamical effect on the sub-tropical and mid-latitude LS ozone (e.g.…”
Section: Influence Of Natural Variability On the Observed Trendmentioning
confidence: 83%
“…No major volcanic eruption occurred during the analysed period, so we disregard this source of variability. The influence of the QBO and ENSO on the hemispheric mean mid-latitude ozone is of the same magnitude, and thus they can both impact LS ozone trends, as shown by the study of Olsen et al (2019). We know from earlier studies that the QBO has a strong dynamical effect on the sub-tropical and mid-latitude LS ozone (e.g.…”
Section: Influence Of Natural Variability On the Observed Trendmentioning
confidence: 83%
“…In a previous work (Ruiz et al, 2021; hereafter R2021), we showed that historical simulations with three chemistry transport models (CTMs) were able to match the interannual surface variations observed in N 2 O. These were clearly driven by the stratospheric quasi-biennial oscillation (QBO), which appears to be the major interannual signal in stratospheric circulation and STE (Kinnersley and Tung, 1999;Baldwin et al, 2001;Olsen et al, 2019). In this work, we calculate the monthly latitudinal STE fluxes of O 3 , N 2 O, and CFCl 3 (F11), establish a coherent picture relating fluxes to observed abundances, and summarize the methods in Sect.…”
Section: Introductionmentioning
confidence: 88%
“…However, retrospectively isolating such associations, which is equivalent to conducting a "perfect model" forecast, does not assure that current operational forecast models can successfully predict those relationships, particularly on subseasonal timescales (e.g., Lavers et al, 2016;Baggett et al, 2017). Nevertheless, some teleconnection and transport patterns appear to be potentially predictable on subseasonal timescales (e.g., Mundhenk et al, 2018;Wang and Robertson, 2019;Pan et al, 2019;DeFlorio et al, 2019;Yamagami and Matsueda, 2020), though these forecasts are typically found to occur during boreal winter.…”
Section: Discussionmentioning
confidence: 99%
“…1 are in part a reflection of the different physical processes that govern them, as outlined above. However, at least a portion of STT and TME seasonality and variability are linked by one important commonality: they are both directly modulated by large-scale Rossby waves (e.g., Ryoo et al, 2013;Albers et al, 2018), which themselves owe their propagation and breaking patterns to the strength and location of the subtropical and polar front jets (Hoskins and Ambrizzi, 1993;Scott and Cammas, 2002;Abatzoglou and Magnusdottir, 2006;Hitchman and Huesmann, 2007;Mundhenk et al, 2016;Olsen et al, 2019). For example, high TME is often observed on the western edge of blocking anticyclones in the North Pacific, where air is rising (Mundhenk et al, 2016), while STT occurs east of the block, where sinking air and PV intrusions frequently develop .…”
Section: Introductionmentioning
confidence: 99%